Essays on regional restructuring and the Polish labour market - Duffy, Fiona (Trinity College (Dublin, Ireland). Department of Economics, 2002)
The fall of the iron curtain and the transition shock that Poland faced in the early 1990s necessitated substantial adjustments throughout the economy. Planners no longer dictated prices, trade, financial allocations or employment levels. The general consensus in the literature was, at least at the start of transition, that the most salient economic adjustments were occurring in the functioning of labour markets. All the Central East European Countries except for the Czech Republic experienced rapidly rising and persistently high (double digit) unemployment rates over the first seven years of transition. A lot of studies have been done on the transition in Central and Eastern Europe and its impact on the labour market. The problem is that most of the studies focused on developments observed at the national level. This of course facilitates cross-country comparisons of experience. At the regional level there was also considerable interest in labour market adjustments across transition countries but data limitations have meant that most of these studies focused on either particular groupings of regions within a country or generalized regional issues across Central and Eastern Europe within a very descriptive analysis. In this thesis I present new evidence concerning labour market adjustments specifically looking at the Polish economy. I apply a new taxonomy of socio-economic development to Polish regions to examine two aspects of regional labour market adjustments, first wages and second employment and unemployment changes. I use micro-level evidence provided by the Polish Central Statistics Office to present three essays on Polish labour market adjustments and regional restructuring.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin